The Debt Policy and Performance of State-Owned Companies in Indonesia - Sinurat, Mangasi; Ilham, Rico Nur; Sinta, Irada; Ahmad, Shabir (Jurnal Manajemen Bisnis, 2024)
Research Aims: This research aims to explore the factors influencing debt policy in "red-license plate" companies in Indonesia from 2010 to 2020. Design/Methodology/Approach: The research method used is empirical studies to achieve the study's objectives.Research Findings: The first analysis result showed that their debt policy was significantly determined by collateral value of assets, profitability, company size, business risk, liquidity. However, those factors partly clarified the policies, whereas other factors outside the observation defined the rest. The result of the second analysis meanwhile showed that the debt policy has significant negative impact on the company performance both long-term and short-term period.Theoretical Contribution/Originality: Several research strategies that may be useful in this respect are discussed, and a typology of constructs is proposed on the basis of this analysis is Short term debt policy, Long term debt policy, and The thermal design power are as latent variables; the collateral value of assets, Profitability, Company size, Business risk, Growth opportunity, and Liquidity are construct variables.Practitioners/Policy Implications: The first stage of analysis is intended to examine the factors influencing debt policy, both total debt policy, short term debt policy, and long-term debt.Research Limitations/Implications: Considering the limited amount of data available, this study conducts a risk assessment based on historical data only. A more complete identification of risks and vulnerabilities will include a forward-looking assessment using sensitivity analysis, scenarios, and testing of debt policies on "state-owned" companies in Indonesia from 2010 to 2020 and the impact of debt policies on the financial performance of companies during that period. We will next explain the methods used to achieve the objectives of the study. Furthermore, it further describes the results of research and discussion and winds up with conclusions and suggestions.